(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2019)
The morphological and growth characteristics of mycelial cultures of 24 xylotrophic medicinal Agaricomycetes mushrooms including 12 edible species collected in Mazandaran and Golestan Provinces of Northern Iran were studied for the first time. The morphology of colonies, growth parameters, and an ability to develop in vitro teleomorph, presence and form of hyphal clamps, cystidia, loops, asexual spores (anamorphs), crystals and other cultural characteristics of Iranian collections were observed. The obtained data can be used for taxonomic identification of mycelial cultures of studied species/strains during their biotechnological cultivation to obtain mycelial biomass and bioactive compounds.